TINDAK KEJAHATAN CYBER CRIME DALAM PERSPEKTIF FIKIH JINAYAH - Gunawan, Hendra (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2020)
Technological progress is an inevitable growth along with the progress of human civilization to make humans integrate without space and time limit in cyberspace, but this technological progress is boarded by people who are not responsible for committing crimes in cyberspace termed cyber crime, then this paper tries to discuss cyber crime from the perspective of Jurisprudence. The main problem in this article is how the jurisprudence perspective of cyber crime, from here the authors formulate a sub-issue namely how the terminology of cyber crime according to jurisprudence jinayah. The method used in this article is descriptive qualitative, sourced from fiqh books and books related to the topics discussed in this article with the method of collecting data using literature studies.The author's findings in this article, that the current form of cyber crime is not spared from jinayah fiqh studies because even though cyber crime is a new crime model, but it has similarities with the cases discussed in jurisprudence, one of the cyber crime crimes is hacking (stealing data) or breaking into an ATM is the same as Syariqah (stealing) only that distinguishes it is the way to do it, so if Syariqah is done in the real world while cyber crime is done in cyberspace. For more details, please look at the next discussion.